The Impact of Environmental, Social, and Governance (ESG) Performance, Leverage, and Cash Flow on Firm Growth - Evy Roslita; Basrah LubiS (ESENSI: Jurnal Manajemen Bisnis, 2025)
This research aims to analyze the impact of Environmental, Social, and Governance (ESG) performance, leverage, and cash flow on company growth, represented by profit growth and asset growth, in firms belonging to the consumer non-cyclicals sector. Using the purposive sampling method, a total of 83 consumer non-cyclicals companies listed on the Indonesia Stock Exchange during 2021–2022 were selected as samples. Based on multiple linear regression analysis, the results show that cash flow has a positive effect on profit growth, while leverage has a negative effect on profit growth. However, Environmental, Social, and Governance performance has no significant effect. Furthermore, the study also finds that all the independent variables observed have no significant effect on company growth as measured by asset growth.